Richard McCormick, SJ, and Dual Epistemology - Clark, Peter A. ([S.l.] SSRN, 2010)
This article will examine McCormick's moral epistemology both at the level of how human persons know values and disvalues, which hereinafter will be referred to as synderesis, and at the level of how human persons know the rightness and wrongness of an action, which hereinafter will be referred to as normative moral judgment. On the one hand, from this investigation it appears that McCormick operates with a dual moral epistemology, at least at the level of synderesis. This means that at one point in time it appears that a significant shift may have occurred in his moral epistemology at the level of synderesis. This may also be true at the level of normative moral judgment. On the other hand, McCormick's moral epistemology may in fact be a synthesis, which is the product of development and maturity in his thought process. This article will articulate, examine, and analyse both moral epistemologies. The first moral epistemology is operative in McCormick's writing up until 1983. The second moral epistemology corresponds to McCormick's decision in 1983 to write primarily in the area of bioethics from a theological perspective. Since the year 1983 seems to be the pivotal time when these two moral epistemologies converge, I will refer to the first moral epistemology as “prior to 1983” and I will refer to the second moral epistemology as “after 1983.” Because of the numerous criticisms that surround McCormick's moral epistemology, and the ambiguity that it entails, McCormick needed to articulate his theoretical foundations clearly and develop them systematically and coherently. Numerous moral theologians called for him to do this, yet he never responded. A systematic understanding of McCormick's moral epistemology is not only necessary but crucial in examining various issues in bioethics. It is necessary because it is the basis of moral decision making. It is crucial because the life and death of individuals may hang in the balance.